Depositional environmental, provenance and climatic signatures of textural characteristics and heavy mineral distribution of the Vaigai river channel bed sediments, Southern India - Ramkumar M.; Juni K.J.; Sreerhishya K.; Meenumol S.; Kaviraj R.; Jyothika J.; Roy Priyadarsi D.; Balasubramani K.; Thirukumaran V.; Nagarajan R.; Menier D.; Mathew M.J. (Geološki Anali Balkanskoga Poluostrva, 2025)
Surface sediments of the river channels provide a proxy to understand contemporary-paleoconditions of sedimentary environments, climate, provenance, etc. Systematic field mapping, and delineation of geological and geomorphic features was conducted, followed by collection of surface sediments from river channels. Laboratory analyses included granulometry, textural statistical parameters, and heavy mineral analysis of 53 sediment samples collected from the entire reach of the Vaigai River from upstream to downstream, the majority of them were coarse sand, moderately sorted, finely skewed and platykurtic. Barring a few aberrations, a gradual increase in roundness of the grains from the headwaters to the basin outlet is recorded in the present study. The transportation of sediments is characterized by suspension with rolling. Discriminant plots of environmental and energy conditions affiliate the studied sediments to the riverine environment and unidirectional flow except few. Recycling of valley‐fill sediments and negligible-noticeable sorting, weak transport characteristics during normal flow and effective exhumation-erosion-deposition during significant flow conditions were interpreted. Among the heavy minerals, the ubiquitous occurrence of hornblende followed by garnet, magnetite, epidote, rutile, zircon, and monazite in the decreasing proportion is documented. Elemental abundances in the heavy minerals of samples from the upper part of the basin show no significant/noticeable enrichment/depletion characteristics, whereas the samples of the lower part of the basin show uniformly abundant Si. These data and interpretations suggests that the channel bed sediments are mostly reworked and recycled, probably influenced by the river’s flow on an antecedent valley and valley-fill. Within this general nature, aberrations are introduced by land use and other anthropogenic factors-imposed changes in sediment size, shape, sorting and heavy mineral occurrence and relative proportions.